"It Was Like a Magnet to Bring People In": School Administrators' Responses to the Gentrification of a Two-Way Bilingual Education (TWBE) Program in Central Texas. Issue 6 (November 2019) - Heiman, Daniel; Murakami, Elizabeth
This critical ethnographic study investigated how gentrification processes shaped an elementary school's community and two-way bilingual education (TWBE) program in Central Texas. Findings revealed how these gentrification processes impacted the principal and vice principal at the ontological and epistemological levels, as their ways of being and knowing around their TWBE program were altered as a dual gentrification process pushed in new customers thirsting for bilingualism and pushed out Spanish-speaking families due to rapidly rising rents. Implications highlight the urgency for administrators to develop critical consciousness around the original race radical vision of bilingual education.